FRI0244 Assessing organ involvement and current symptoms as indicators for disease progression in 3047 patient cohort. (23rd January 2014) - Moinzadeh, P.; Hunzelmann, N.; Krieg, T.; Blank, N.; Fierlbeck, G.; Genth, E.; Kötter, I.; Kreuter, A.; Melchers, I.; Pfeiffer, C.; Müller-Ladner, U.; Riemekasten, G.; et al.
Abstract : Background: To improve detection and follow-up of patients with systemic sclerosis, the German Network for Systemic Scleroderma (DNSS) was founded and initiated a registry gathering information on diagnosis, clinical symptoms and therapy of SSc patients. Methods: Up to date, more than 3000 patients have been grouped into four descriptive disease subsets, i.e. limited cutaneous disease (lcSSc), diffuse cutaneous disease (dcSSc), overlap-syndrome and undifferentiated connective tissue disease (UCTD) with scleroderma features. Disease progress between initial patient registration (year 0) and fourth follow-up (year 4) was measured using organ involvement and present symptoms as indicators. Results: Recent analyses revealed that 49% of patients suffer from limited SSc (lSSc), 31% from diffuse SSc (dSSc) and 10% of patients were diagnosed with an overlap-syndrome. 8% had an undifferentiated form while Scleroderma sine scleroderma was present in 0.7% of patients. Follow-up data are available from 1595 patients after one year, from 901 patients followed for two years, 573 patients followed for three years and 386 followed for at least four years. After four years a significant increase was detected in the frequency of pulmonary hypertension (PAH) (14.4% to 24.2%, p=0.001), lung fibrosis (38.8% to 47.6%, p=0.006), oesophagus involvement (58.5% to 74.8%, p=0.0001), bowel involvement (13.6% to 19.9%, p=0.03), Kidney (10.7% to 15.8%, p=0.03) and Heart (13.4% to 24.0%, p<0.0001) involvement. Disease subsets were associated with different organs being more frequently involved, i.e. lcSSc with PAH (13.5% to 25.0%, p=0.007), oesophagus (60.7% to 77.0%, p=0.0001) and colon involvement (7.3% to 11.6%, p=0.002); dcSSc with PAH (19.0% vs. 25.9%, p=0.035), lung fibrosis (63.5% vs. 71.4%, p=0.02) and heart involvement (19.1% vs. 27.7%, p=0.007). Interestingly, patients with overlap syndrome showed no significant change in organ involvement over time. Conclusions: After four years of follow-up in a large well defined SSc cohort, a significant increase in frequency of organ involvement was observed, particularly with respect to the lung, GI-tract and heart. Patients with SSc should be followed at least annually for organ involvement, the frequency of follow-ups being increased depending on the disease activity. Disclosure of Interest: None Declared